2015
DOI: 10.3389/fnmol.2015.00074
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Induction by Endothelial-Monocyte Activating Polypeptide II Contributes to the Inhibition of Malignant Biological Behaviors by the Combination of EMAP II with Rapamycin in Human Glioblastoma

Abstract: This study aims to investigate the effect of endothelial-monocyte activating polypeptide II (EMAP II) on human glioblastoma (GBM) cells and glioblastoma stem cells (GSCs) as well as its possible mechanisms. In this study, EMAP II inhibited the cell viability and decreased the mitochondrial membrane potential in human GBM cells and GSCs, and autophagy inhibitor 3-methyl adenine (3-MA) blocked these effects. Autophagic vacuoles were formed in these cells after EMAP II treatment and this phenomenon was blocked by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…It suggested that the role of autophagy in the regulation of cell migration possibly mediated by the inhibition of TGF‐β signaling. Previous reports concerning the role of autophagy in glioma cell migration appeared to be controversial . Our results implicated that the regulation of autophagy on cell migration was context dependent, differing with cells types or stimuli.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It suggested that the role of autophagy in the regulation of cell migration possibly mediated by the inhibition of TGF‐β signaling. Previous reports concerning the role of autophagy in glioma cell migration appeared to be controversial . Our results implicated that the regulation of autophagy on cell migration was context dependent, differing with cells types or stimuli.…”
Section: Discussionsupporting
confidence: 55%
“…It suggested that the role of autophagy in the regulation of cell migration possibly mediated by the inhibition of TGF-b signaling. Previous reports concerning the role of autophagy in glioma cell migration appeared to be controversial [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to other studies, various therapeutic drugs could enhance autophagic cell death in glioblastomas, such as thalidomide (Gao et al, 2009) and vitamin (Bak et al, 2016). Several previous studies suggested that EMAP-II inhibited the cell viability of GSCs via inducing autophagy rather than inducing apoptosis (Ma et al, 2015; Chen et al, 2016). In addition, TMZ-induced autophagy and apoptosis inhibited the cell viability of human glioma cells (Chen et al, 2015; Yu et al, 2015b).…”
Section: Discussionmentioning
confidence: 93%
“…When combined with thalidomide, a drug could induce autophagy, the cytotoxicity of TMZ to glioma cells was enhanced by autophagy (Gao et al, 2009). Combination of EMAP-II with Rapamycin induces GSCs autophagy and then inhibits the malignant biological behaviors of GSCs (Ma et al, 2015). Therefore, we speculated EMAP-II-induced autophagy might could enhance the antitumor capacity of TMZ.…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of the PI3K/Akt pathway prevents the translocation of damageregulated autophagy modulator to the mitochondria and induces apoptosis in hepatocellular carcinoma cells by the mediation of mitophagy (41). Furthermore, inhibition of the PI3K/Akt/mTOR signaling pathway is accompanied by autophagy and mitophagy in human glioblastoma cells, glioblastoma stem cells and human prostate cancer (42,43). In the present study, the results indicated that 17β-E2 regulated mitophagy in INS-1 cells through the GPER/PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%